Live Imaging of Host-Pathogen Interactions in Zebrafish Larvae - Matty, Molly A; Oehlers, Stefan H; Tobin, David M (Methods in molecular biology (Clifton, N.J.), 2016)
Zebrafish larvae are a powerful platform for studying the innate immune response to infection. The small size and optical transparency of larval zebrafish allow for multiple subject, multidimensional, and longitudinal imaging experiments. This chapter describes protocols for infecting zebrafish larvae with their natural pathogen Mycobacterium marinum, rapid short-term imaging, long-term extended imaging, and drug treatment assays. These protocols can be easily adapted to image and manipulate host interactions with other pathogens.